Supplementary data for the mediation effect of personality functioning – Gender differences, separate analyses of depression and anxiety symptoms and inferential statistics of the relationship between personality functioning and different types of child maltreatment - Anna Freier; Johannes Kruse; Bjarne Schmalbach; Sandra Zara; Samuel Werner; Elmar Brähler; Jörg M. Fegert; Hanna Kampling (Data in Brief, 2022)
This article provides supplementary data for the original research article ‘The Mediation Effect of Personality Functioning Between Different Types of Child Maltreatment and the Development of Depression/Anxiety Symptoms – a German Representative Study’ [1]. The representative data were acquired as part of a broader survey on different aspects of mental health in the German population. This supplementary data article contains the statistical analyses of the relationship between the different subtypes of child maltreatment (CM) and impairments of personality functioning, which were only presented as a diagram in the original article. Additionally, the analyses conducted separately for symptoms of depression and anxiety as well as gender are provided. For the mediation analyses, the variables of depression/anxiety symptoms, personality functioning and CM types were standardized. The data may be useful for discussion, further insights and as a starting point for the development of further studies.